Entrepreneurship Education in the Transformation of Incarcerated Individuals: A Review of the Literature and Future Research Directions: - Grosholz, Jessica M. (International journal of offender therapy and comparative criminology, 2020)
This article draws upon the theories of entrepreneurial cognition, planned behavior, and criminal desistance to understand the role of entrepreneurship education in the behavioral and cognitive transformation of incarcerated individuals. Specifically, this article considers how participation in an entrepreneurship education program should influence entrepreneurial opportunity recognition, cognitive transformation, and institutional misconduct. It suggests these changes are more likely to influence an incarcerated person’s entrepreneurial intentions and criminal desistance. The six propositions presented shed light on how an incarcerated individual’s willingness to change his or her attitudes and develop an entrepreneurial mind-set influence his or her behavior in prison and prepares him or her to prosper in a dynamic and complex world after release. This article argues that the study of one’s transformation while incarcerated through the discovery, evaluation, and exploitation of opportunities is likely to advance empirical and theoretical perspectives of the fields of entrepreneurship. The examination of how incarcerated persons deal with fear of failure, risk aversion, and identity, in particular, presents great opportunities for future research.